Shelley's CENCI : Scorpions Ringed with Fire - Curran, Stuart (Book collections on Project MUSE., 1970)
Shelley's tragedy, The Cenci, has been regarded as an avant-garde attack on orthodox Christian principles, a celebrated cause for Victorian intellectuals, a vehicle for innovative minds of the theater, a historical oddity, a neglected masterpiece. Derived from the dark legends of one of Rome's great families, the Cenci records a history of sadism, incest, and murder.Shelley's one actable play has received little attention in modern times. Professor Curran studies it first as a poem-its patterns, themes, imagery-then as a play. After showing its relationship to England's Regency theater, he analyzes the fascinating course of its stage history, and finds Shelley foreshadowing such modern emphases as psychodrama, the existential vision, the Theatre of Cruelty.Originally published in 1970.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.